POLITICAL COMMUNICATION PROCESS IN THE FACTIONALISM OF ISLAMIC POLITICAL PARTIES: CASE STUDY OF PROSPEROUS JUSTICE PARTY (PKS) (1999-2023) - Anna Kurniawati; Arief Subhan; Morissan (International Journal of Social Science, 2024)
This research wants to know the process of political communication in factionalism that occurs in Islamic Parties, namely Prosperous Justice Party (PKS). The approach taken in this research is qualitative with case study research type and interview method as data collection technique. Interviews were conducted with 12 (twelve) resource persons. The theories used in this research are political communication theory, conflict theory, and faction theory. The results showed that there are stages in Prosperous Justice Party factionalism, namely cooperative factionalism, competitive factionalism, and degenerative factionalism. In these three stages, each stage was analyzed in accordance with the elements of political communication, namely sender, encoding, message, channel, decoding, receiver, feedback, and noise. In the cooperative factionalism stage, there are justice and welfare factions. At the competitive factionalism stage, there are conflicts between factions and at the degenerative factionalism stage marked by the birth of a new party, namely the Gelombang Rakyat Indonesia party. The generation system in Prosperous Justice Party as a recipient communication element, palys a role in political communication and strengthens the party’s ability to overcome persistent conflicts and has saved the party from prolonged conflict. In addition to regeneration, PKS leaders and the Majelis Syuro as sender elements or communicators, have a central role in the political communication process. Their role covers various aspects, from formulating party messages to communicating with the public, party members, and other stakeholders.